"Who Will Take Charge of Africa?”: Brazil and Mozambique in the Context of South-South Cooperation Projects - Silva, Sandro José da (2024)
This article describes the social construction of Brazil’s position in the agribusiness sector in Mozambique as a neocolonial initiative toward emerging economies, especially reproduction of economic and political strategies of central countries aimed at controlling territorial dominance. The study of these complex relationships helps to understand Brazil’s place in this new scenario, in which the power Global South countries appears as the political backyard of global economies, seeking to reposition Brazil’s image as a racial laboratory for reinventing peoples, hierarchies and borders. The category of “cooperation” “serves as a smokescreen in Brazil’s territorial expansion policy toward the African country, as well as parallel cultural efforts, with the goal of reshaping historical relations between the nations. It is concluded that Brazil seeks to reshape its role in South-South relations, bringing with it authoritarian and racial dimensions that structure these relations.